Fabrics in Colour: Knidos. The Hellenistic and Early Imperial Tableware - Kögler, Patricia (Journal of Hellenistic Pottery and Material Culture, 2022)
Current ceramic research is increasingly concerned with the economic, cultural and social aspects of Hellenistic and Imperial pottery. The ability to identify and determine the origin of ceramics based on specific properties of clay and coating is more than ever a sine qua non for every researcher in this field. The macroscopic analysis by the trained eye of the expert is still the most important method for assessing the sherd material. Although today it is possible to identify and classify pottery by means of archaeometric and chemical analyses, this can only be of secondary importance, as the corresponding methods are complex and expensive and therefore cannot be applied to the necessary extent to the enormous quantities of finds.